고농도 염소 가스 환경에서의 합금 종류에 따른 부식 거동 연구 - 한덕현; Deokhyun Han; 정우철; Woo-chul Jung; 공만식; Man-sik Kong (Corrosion science and technology, 2025)
High-concentration chlorine (Cl 2 ) gas is widely used in industries such as chemical processing, pharmaceuticals, electronics manufacturing, and gas treatment. Due to its highly reactive nature, it can also accelerate material degradation, leading to reduced equipment durability and increased maintenance costs. Understanding the corrosion behavior of different alloys in Cl 2 environments is crucial for enhancing process stability and extending equipment lifespan. This study analyzed corrosion behaviors of Co-Ni-Cr, Co-Cr-Ni, Fe-Cr-Ni, Cu, and Zn-Al-Cu alloys in high-concentration Cl 2 gas environments. Results revealed that Co-Ni-Cr and Co-Cr-Ni alloys exhibited superior corrosion resistance due to formation of stable Cr 2 O 3 protective layers, whereas Fe-Cr-Ni alloys provided intermediate resistance. Cu and Zn-Al-Cu alloys showed varying corrosion behaviors depending on environmental factors such as humidity and oxide layer stability. These findings emphasize the critical role of alloy composition and protective oxide layers in reducing Cl 2 -induced corrosion. By providing a comprehensive analysis of different alloy systems, this study provides insights into optimizing material selection for Cl 2 gas applications, contributing to improved industrial process stability and enhanced durability.